(Nbnsu(B-(NYN hOJD sOLONGOS RUU QWUULV BUJ GADAAD BODLOGO(B.-s (NmAGISTRYN AVIL(B: s - (N|NHSAJHAN g(B.s; (NmONGOL uLSYN iH sURGUULXs ((Nub(B.:s, 2013)
English
(NdIP(B-4690s
Keywords: (NMAGISTRYN DIPLOMYN AVILs; (NOLON ULSYN HARILCAAs; (Nbnsus; (NhOJD sOLONGOSs